SLEEP DEPRIVATION REDUCES COGNITIVE PERFORMANCE – A REVIEW - Dr Sridevi.G (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Sleep is vital for each living organism to regain the optimal health and well being. The optimal duration of sleep is high in infants around 12-16 hrs a day, teens around 8-10 hours and adults and older people require 7-8 hrs/ day. Sleep deprivation suppresses the immune system, increases the risk of hypertension and Diabetes mellitus, influences the secretion of growth hormone, testosterone and cortisol. The influence of sleep deprivation on brain structures modulates the activity of the central nervous system, decreased alertness and concentration, decreased reaction time and impaired ability to focus on timed tasks. Sleep deprivation is disruptive to working memory and executive processing in the prefrontal cortex of the brain. The communication between prefrontal cortex and hippocampus are areas involved in consolidation of long-term memory consolidation and this connection is abolished in sleep deprivation. Sleep deprivation has profound effects on higher cognitive skills of a person. So, sufficient sleep is strongly recommended for normal well-eing of all living organisms irrespective of age, sex and species.